(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Rapid urbanization in Gurugram, India, has led to traffic congestion, poor service, and increased pollution in the city's transportation system. Commuters increasingly rely on private and intermediate forms of transportation due to the need for more public transit. Visum, a macrosimulation program, was used to construct a four-stage sequential public transport model in Gurugram. The model was developed with the use of 1124 survey results. After the travel demand model was made, it was used to estimate the number of trips people and groups took in the baseline year using public and private modes of transportation. The results were verified using empirical evidence. To promote environmentally friendly transportation, the Gurugram metro was integrated with feeder modes and park-and-ride lots. The advantages of this were examined at the network level. After implementing multi-modal integration, metro rail usage increased. The long-term goal of this work is to get people out of their vehicles and onto public transit.